Quantifying Micro-mechanical Properties of Soft Biological Tissues with Scanning Acoustic Microscopy - Zhao, Xuegen (2011)
In this study we have established a new approach to more accurately map acoustic wave speed (which is a measure of stiffness) within soft biological tissues at micrometer length scales using scanning acoustic microscopy. By using thin (5 μm thick) histological sections of human skin and porcine cartilage, this method exploits the phase information preserved in the interference between acoustic waves reflected from the substrate surface as well as internal reflections from the acoustic lens. A stack of images were taken with the focus point of acoustic lens positioned at or above the substrate surface, and processed pixel by pixel using custom software developed with LABVIEW and IMAQ (National Instruments) to extract phase information. Scanning parameters, such as acoustic wave frequency and gate position were optimized to get reasonable phase and lateral resolution. The contribution from substrate inclination or uneven scanning surface was removed prior to further processing. The wave attenuation was also obtained from these images.